Sistem Penyiraman Otomatis Menggunakan Sensor Kelembaban Tanah Berbasis Mikrokontroler Arduino Mega 2560 Pada Tanaman Mangga Harum Manis Buleleng Bali - Rahardjo, Pratolo (Majalah Ilmiah Teknologi Elektro, 2022)
Abstract — In the development of technology, the application of automated systems began to bloom applied in various fields. The automatic system is able to provide convenience in its application, both in terms of time and energy efficiency. In general, an automatic system can be interpreted as a system that is capable of carrying out a job without human intervention. researchers designed a device that is able to work automatically to water the plants based on the soil conditions of the plants. an automated system designed by researchers using the Arduino Mega 2560 microcontroller as the main control and soil moisture sensor to detect soil moisture levels. The process of watering plants occurs based on the level of humidity that has been detected by a soil moisture sensor. Result of the tests on this research, the watering process is carried out when the soil moisture level is less than 20%. Meanwhile, when the soil moisture level is more than 20%, the watering process will stop.